High-Intensity Interval Training Restores Glycolipid Metabolism and Mitochondrial Function in Skeletal Muscle of Mice With Type 2 Diabetes - Zheng, Lifang; Rao, Zhijian; Guo, Yifan; Chen, Peijie; Xiao, Weihua (Frontiers in Endocrinology, 2020)
High-intensity interval training has been reported to lower fasting blood glucose and improve insulin resistance of type 2 diabetes without clear underlying mechanisms. The purpose of this study was to investigate the effect of high-intensity interval training on the glycolipid metabolism and mitochondrial dynamics in skeletal muscle of high-fat diet (HFD) and one-time 100mg/kg streptozocin intraperitoneal injection-induced type 2 diabetes mellitus (T2DM) mice. Our results confirmed that high-intensity interval training reduced the body weight, fat mass, fasting blood glucose and serum insulin of the T2DM mice. High-intensity interval training also improved glucose tolerance and insulin tolerance of the T2DM mice. Moreover, we found that high-intensity interval training also decreased lipid accumulation and increased glycogen synthesis in skeletal muscle of the T2DM mice. Ultrastructural analysis of the mitochondria showed that mitochondrial morphology and quantity were improved after 8 weeks of high-intensity interval training. Western blot analysis showed that the expression of mitochondrial biosynthesis related proteins and mitochondrial dynamics related proteins in high-intensity interval trained mice in skeletal muscle were enhanced. Taken together, these data suggest high-intensity interval training improved fasting blood glucose and glucose homeostasis possibly by ameliorating glycolipid metabolism and mitochondrial dynamics in skeletal muscle of the T2DM mice.